Adding tactile feedback increases avatar ownership and makes virtual reality more effective at reducing pain in a randomized crossover study - Hoffman, Hunter; Fontenot, Miles R.; Garcia-Palacios, Azucena; Greenleaf, Walter J.; Alhalabi, Wadee; Curatolo, Michele; Flor, Herta (Scientific reports, 2023)
Severe pain is a widespread health problem in need of novel treatment approaches. In the current study we used real water to give virtual objects (i.e., animated virtual water) more realistic physical properties (wet liquid qualities). Healthy volunteers aged 18-34 participated in a within-subject randomized study comparing participants’ worst pain during brief thermal stimuli with (1) No Immersive Virtual Reality (VR), versus (2) during VR + no tactile feedback versus (3) VR + real water (with tactile feedback from co-located real objects). Tactile feedback significantly decreased pain intensity (VR analgesia, p < 0.01), compared to VR with no tactile feedback, and compared to No VR (baseline). Tactile feedback made the virtual water feel significantly more real, increased participant’s sense of presence, and both VR conditions were distracting (significantly reduced accuracy on an attention demanding task). As a non-pharmacologic analgesic, mixed reality reduced pain by 35% in the current study, comparable to the analgesia from a moderate dose of hydromorphone in previous published experimental studies. Tactile feedback also significantly increased avatar embodiment, the participants illusion of ownership of the virtual hands, which has potential to improve the effectiveness of avatar therapy for chronic pain in future studies. Mixed reality should be tested as treatment in pain patients.
Veröffentlicht: 22. Mai 2023
Gesehen am 09.11.2023